2020
DOI: 10.34117/bjdv6n4-283
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento inicial de mudas de mogno africano em função de susbtratos e lâminas de irrigação

Abstract: In recent years, in the Brazilian Savannah, there is a growing interest in the cultivation of tree species, which stand out for their environmental and commercial importance. The objective of this work was to evaluate the initial growth of African mahogany (Khaya ivorensis) plants on substrates and irrigation levels and to select the productive characteristics that result in ideal conditions for production .The experiment was installed in a randomized block design, with four replications, in split-plot, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
1
1
1
Order By: Relevance
“…As a result, whether the substrate is not very aerated due to overwatering, this stagnant water causes a typical stress situation by restricting free diffusion of oxygen from air to germinating seeds or even inhibiting germination (NARSAI et al, 2015, MARCOS FILHO, 2005. On the contrary of our findings, OLIVEIRA et al (2020) found positive effect of a mixture of 45% red soil + 45% sand + 10% chicken manure substrate on seedling growth of Khaya ivorensis (Meliaceae).…”
Section: Resultscontrasting
confidence: 99%
“…As a result, whether the substrate is not very aerated due to overwatering, this stagnant water causes a typical stress situation by restricting free diffusion of oxygen from air to germinating seeds or even inhibiting germination (NARSAI et al, 2015, MARCOS FILHO, 2005. On the contrary of our findings, OLIVEIRA et al (2020) found positive effect of a mixture of 45% red soil + 45% sand + 10% chicken manure substrate on seedling growth of Khaya ivorensis (Meliaceae).…”
Section: Resultscontrasting
confidence: 99%
“…This behavior has already been reported in several studies where other metals such as Cr, Cu, and Zn have been shown to directly affect the activity of the nitrate reductase enzyme, especially when found in high concentrations, thus affecting the main input of nitric nitrogen in plant metabolism. Another important interference of this metal seems to be related to the imbalance of homeostatic function and plant development Moraes;Conceição;Oliveira;Okumura;Silva;Oliveira Neto, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…É comum na literatura trabalhos que reportam frequências de irrigação e frações de reposição diversas, com variação de uma irrigação diária até doze vezes ao dia em espécies distintas [10,16,17,18,19] entretanto, torna-se inviável uma frequência reduzida associada ao uso de hidrogel, pois, segundo [20] o custo de produção e plantio com uso do hidrogel é menor em estações secas. Ou seja, na produção de mudas em substratos comerciais, parece inconsistente o uso de doses de polímero hidroabsorvente com irrigações frequentes ou diárias visando manter a umidade elevada.…”
Section: Introductionunclassified